Contrast-Enhanced Ultrasound (CEUS) in Pregnancy: A Comprehensive Review of Clinical Applications - Begaj, Kaltra; Sperr, Andreas Georg; Clevert, Dirk Andre (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2026)
Imaging during pregnancy presents unique challenges. Computed tomography (CT) is generally avoided due to fetal radiation exposure, and magnetic resonance imaging (MRI) may be limited by concerns regarding gadolinium-based contrast agents. As a result, ultrasound (US) remains the primary imaging tool during pregnancy. Contrast-enhanced ultrasound (CEUS) expands the diagnostic capabilities of conventional US by providing real-time vascular information comparable to contrast-enhanced CT or MRI. Importantly, microbubble contrast agents used in CEUS do not cross the placenta and have shown no fetal harm in clinical studies. Nevertheless, CEUS remains an off-label technique during pregnancy, underscoring the need for a comprehensive review of the available literature to assess its safety and clinical applications during pregnancy.This review summarizes the current evidence up to 2025 on the use of CEUS in pregnancy and highlights its clinical value with respect to evaluating acute and chronic maternal conditions – including oncologic, vascular, infectious, inflammatory, and other organ-specific pathologies – illustrated through representative case examples. Clinical studies, case reports, and international guidelines were analyzed with a focus on safety and diagnostic performance.Although still off-label, CEUS demonstrates an excellent safety profile and high diagnostic utility when clinically indicated in pregnancy. No maternal, fetal, or neonatal adverse effects have been reported, and no placental transfer of microbubbles has been demonstrated. CEUS enables high-resolution assessment of abdominal organs, vascular pathologies, and inflammatory or infectious changes, reducing the need for ionizing or gadolinium-based imaging. It represents a safe, effective, and radiation-free diagnostic alternative when conventional imaging is limited.
Keywords: pregnancy; safety; microbubbles; contrast-enhanced ultrasound (CEUS)